Pelatihan Literasi Dasar bagi Anak-Anak Melalui Program Pendidikan Komunitas untuk Mewujudkan Generasi Cerdas di Kota Pdangsidimpuan - Riskiana aritonang, Devinna; Shoufi Nisma Dewi; Khairunnisah; Batubara, Melvariani Syari; Lisda Khairani; Rodiah Ulfa (PAKAT: Jurnal Pengabdian Kepada Masyarakat, 2025)
Basic literacy skills are fundamental in developing high-quality human resources from an early age. However, many children in Padangsidimpuan still face difficulties in recognizing letters, reading syllables, and understanding simple texts. This study aims to analyze the effectiveness of basic literacy training through a community-based education program in improving children’s early literacy abilities. The research employed a quantitative descriptive method using a one-group pretest–posttest design. The subjects consisted of 20 children who participated in four sessions of literacy training. Data were collected through literacy tests covering letter recognition, syllable reading, and comprehension of short texts. The data were analyzed by comparing the pretest and post-test results. The findings show a significant improvement in all aspects of basic literacy. The average pretest score of 56 increased to 82 in the post-test. Children also demonstrated higher learning motivation, engagement, and self-confidence throughout the program. The community-based education approach successfully created a fun, meaningful, and participatory learning environment, making it a promising solution to the low literacy skills among children in the area. In conclusion, basic literacy training through community education programs is effective in supporting the development of early reading skills in children and is feasible to be replicated in other communities. This study highlights the importance of collaboration between the community, parents, and educators in realizing an intelligent young generation in Padangsidimpuan.